Analisis Inovasi Produk pada Pengembangan Brand Asliori dalam Meningkatkan Daya Saing Bisnis (Lembaga Pengembangan Kinerja Dosen, 2025)
Product innovation is a key factor in increasing business competitiveness amidst increasingly fierce global competition. This research analyzes the role of product innovation on a company's competitive advantage. This study highlights how new product development, feature differentiation, and quality improvement can strengthen a company's position in the market. The research results show that companies that consistently adopt innovation strategies are able to increase market share, customer loyalty and profitability. Apart from that, collaboration between departments, the use of cutting-edge technology, and response to consumer needs also play an important role in the success of innovation. The implications of this research emphasize the importance of a culture of innovation and sustainable investment in research and development as the key to winning business competition in various industries.